Shaping the competitive advantages of travel agencies over online services in today’s environment - E. A. Frolova (Вестник университета)
The object of the study is the modern tourism and hospitality industry, which has faced significant losses and transformations over the past few years. Changes in the service system, transition to new standards, introduction of digital and online technologies in operations, etc. are affecting both industry players and consumer preferences. While some consumers only use the services of professional travel organisers, others travel on their own, preferring independent tourism. The article examines major trends in the tourism industry, reviews the market and gives recommendations on what challenges and opportunities to create a competitive advantage over online resources, aggregators in the fight for the consumer should pay attention to travel agencies as one of the key players in the market of travel services.